Covid-19: An ad hoc public health ethics consultation Covid-19: Eine Ad hoc Public-Health-Ethikberatung - Wild, Verina; Buyx, Alena; Hurst, Samia; Munthe, Christian; Rid, Annette; Schroeder-Baeck, Peter; Strech, Daniel; Thompson, Alison (Gesundheitswesen, 2020)
In this paper we describe the process and content of our ad hoc public health ethics consultation for a Bavarian health authority in relation to Covid-19.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Covid-19; Public health ethics; SARS-CoV-2